Review: The Role of Human Papillomavirus in Virus-Induced Carcinogenesis - Zahraa, M Essam; L, Al-Khalaileh (Journal of Cervical Cancer, 2025)
Viral infections contribute to a significant proportion of human cancers, with human papillomavirus (HPV) being one of the most well-established oncogenic viruses. This review summarizes HPV biology, transmission, classification, molecular mechanisms of carcinogenesis, epidemiology of HPV-associated cancers, and current and emerging preventive and therapeutic approaches. particularly HPV-16 and HPV-18, drives malignant transformation through the E6 and E7 oncoproteins, which disrupt tumor suppressor pathways p53 and Rb. Prophylactic vaccination programs have demonstrated remarkable success in reducing HPV-related disease burden, but disparities in coverage remain. Cutting-edge strategies such as CRISPR/Cas9 and RNA-based therapeutics offer promising avenues for treating established infections. Integrating these biomedical advances with robust public health initiatives is essential to ultimately eliminate HPV-associated cancers worldwide (Figure1).
Keywords: Human papillomavirus; cancer; CRISPR